Developing effective strategic communication for sustainable strategic implementation performance - Ali, Albadri Albaloula; Aldogiher, Abdulrahman Saleh (International Journal of Innovative Research and Scientific Studies, 2025)
The study’s objective is to examine strategy communication (SC) issues during the strategy implementation (SI) process and how to set up effective SC for sustainable implementation performance. The methodology is based on a review of the literature and an examination of related studies that have addressed the impact of SC on SI. The study found that SC is one of the top ten factors that influence SI, either positively or negatively. Some research emphasized communication and its elements as an individual factor, while others attributed the impact to communication characteristics. Also, the majority of those to whom SC is directed are from corporate or top management to lower managers, and occasionally to non-managerial levels. Some research has identified the SC tools and methods employed, whereas others have not. The number of examined studies is minimal, which limits the findings. The implication is that selected studies examined many types of organizations, which broadens the scope to include numerous industries of varying characteristics. This study examines SC alone as a factor affecting the SI process, whereas several earlier studies, if not all, looked at SC in conjunction with other relevant factors. The framework and model have added value to the strategy management field.